Women leadership and employee satisfaction in the United Arab Emirates - Al Ghafry, Mai Hamdan Nasser H. Bin (2011)
"Leadership has been considered as a one of the significant skills to exist or to be adopted by the individuals in order to achieve success. Many organizations nowadays are looking to recruit those who have leadership skills that would motivate and influence the employees to innovate and work hard to achieve the organization‟s vision and goals. This dissertation paper will focus on the women leadership in particular in the context of UAE. Also, it shall revolve around the major objective of gaining a more in-depth understanding of leadership of women in UAE, their changing roles in the business and how they shape their work environment and employees perspective. The basic premise of this dissertation study is centered on a discussion on women leadership skills and how they affect the level of job satisfaction of their subordinates in the context of the United Arab Emirates‟ culture. After gathering substantial details on the collated and gathered research evidence from various sources, the quantitative studies were conducted which involved a combination of descriptive and exploratory types of research studies which were conducted using the floating of survey questionnaires with the chosen respondents. The self-administrated questionnaire was distributed at random to a sample of 500 hundred employees. The qualified ones for this paper were 362 respondents whom are led by a woman. After gathering and analyzing the views on the status of women leadership and the level of its influence on their job, the finding shows that there is a positive and significant relationship between women leadership and employee satisfaction. Based on the findings, this paper shall draw the attention to the importance of empowering women in the context of the UAE in which more in depth research need to be done in order to improve the perception of the same. In addition to that, set of recommendations will be provide on how to increase the effectiveness of women leadership in order to achieve high level of employee job satisfaction which will result in achieving any organization objectives successfully and satisfactory."